Insights into the evolutionary dynamics of Neotropical biomes from the phylogeography and paleodistribution modeling of Bromelia balansae - Leal, Bárbara S. S. [UNESP]; Medeiros, Lilian R. [UNESP]; Peres, Elen A.; Sobral–Souza, Thadeu [UNESP]; Palma-Silva, Clarisse [UNESP]; Romero, Gustavo Q.; Carareto, Claudia M. A. [UNESP] (Wiley, 2018)
Premise of the Study: Historical abiotic and biotic factors have strongly affected species diversification and speciation. Although pre-Pleistocene events have been linked to the divergence of several Neotropical organisms, studies have highlighted a more prominent role of Pleistocene climatic oscillations in shaping current patterns of genetic variation of plants. Methods: We performed phylogeographic analyses based on plastidial markers and modeled the current distribution and paleodistribution of Bromelia balansae (Bromeliaceae), an herbaceous species with a wide geographical distribution in South America, to infer the processes underlying its evolutionary history. Key Results: Combined molecular and paleodistributional modeling analyses indicated retraction during the Last Glacial Maximum followed by interglacial expansion. Populations occurring in the semideciduous Atlantic Forest and the Cerrado formed two distinct genetic clusters, which have been historically or ecologically isolated since late Pliocene to early Pleistocene. Populations located in the transition zone had higher levels of genetic diversity, as expected by the long-term climatic stability in the region detected in our ecological niche models. Conclusions: Our study adds important information on how herbaceous species have been affected by past climate in Central and Southeast Brazil, helping to disentangle the complex processes that have triggered the evolution of Neotropical biota.
Keywords: Atlantic Forest; Bromeliaceae; Cerrado; Diversification; Haplotype network; Neotropics; Niche modeling; Quaternary climate oscillations